Life-cycle-Based (LCB) online acquisition framework for supporting Mass Customisation (MC) in practice. - Tang, S. J.; Tjahjono, Benny; Kay, John M. (Cranfield University, 2006)
Mass Customisation (MC) has been perceived in many articles as a strategy of choice for any company. However, Mass Customisation (MC) can be easily discussed at a strategic level; but it is rather more complicated to undertake it organisationally and operationally. The aim of this paper is to explore an effective framework that can support the development of Mass Customisation approaches. Two main contributions are addressed in this paper. One is to prove the insufficiency of current Value-Chain-Based (VCB) MC approaches by using empirical evidence; the other is to propose an online Life-Cycle-Based (LCB) acquisition framework which can be used for developing more comprehensive MC approaches.
Keywords: Mass customisation; Evolutionary acquisition; Life-Cycle-Based; Acquisition framework